2012
DOI: 10.4103/0970-0358.101333
|View full text |Cite
|
Sign up to set email alerts
|

A novel and accurate technique of photographic wound measurement

Abstract: Context:Wound measurement is an important aspect of wound management. Though there are many techniques to measure wounds, most of them are either cumbersome or too expensive.Aims:To introduce a simple and accurate technique by which wounds can be accurately measured.Settings and Design:This is a comparative study of 10 patients whose wounds were measured by three techniques, i.e. ruler, graph and our technique.Materials and Methods:The graph method was taken as the control measurement. The extent of deviation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…Rogers et al found that the simple ruler method overestimated the wound area by an average of 41% compared with digital planimetry. Similarly, Shetty et al reported 29–43% overestimation by the simple ruler method compared with manual planimetry. Both studies, however, evaluated only a small number of wounds ( n = 10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rogers et al found that the simple ruler method overestimated the wound area by an average of 41% compared with digital planimetry. Similarly, Shetty et al reported 29–43% overestimation by the simple ruler method compared with manual planimetry. Both studies, however, evaluated only a small number of wounds ( n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…Wound measurement strategies have traditionally focused on two‐dimensional methods. The simple ruler method often overestimates the wound area and is inappropriate in large wounds with irregular boundaries, but it is fast, easy to use and inexpensive . The elliptical method is also easy to use and inexpensive and is useful for measuring ellipse‐shaped wounds .…”
Section: Discussionmentioning
confidence: 99%
“…3,4,7 Thus, an ellipse formula (length x width x 0.785) is suggested to measure the area 3,4,19 ; however, using this formula assumes that the wound's shape is ellipse. 20 •It has an uncertain accuracy, 12,13,21,22 especially with larger size and irregular shape wound. 3,13 •It is a contact method, has risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the largest mean difference to be in the forearm, which is the most curved body part in this study. Difficulties in measurement of wound surface area of curved body parts is a well‐known problem . However, the mean differences in this study were all negligibly small.…”
Section: Discussionmentioning
confidence: 58%